China’s soft power (non) expansion in the MENA region - Razan Shawamreh (Cogent Social Sciences)
This article examines China’s soft power strategy in the MENA region, which I argue are qualitatively unsubstantial, quantitatively limited, and inherently selective. As part of its broader aspirations to become a/the leading global power, China seeks to enhance its soft power. However, its efforts in this domain across the region primarily focus on lightweight educational collaborations rather than comprehensive and deep knowledge integration that reflects its global ambition. In this context, the prefix ‘non’ in the title signifies the gap between China’s aspiration for global cultural outreach and the reality of its slow-moving initiatives, which often fall short of achieving the depth and scope expected of a truly transformative soft power strategy. Using Joseph Nye’s conceptualization of soft power as a benchmark, the research highlights the establishment of Confucius Institutes, cultural agreements, and university collaborations to examine China’s soft power strategy that basically prioritizes partnerships with specific countries, such as Israel and Egypt, based on economic and technological considerations. Within this examination of the scope and depth of China’s soft power endeavors, the article critically explores whether China’s selective approach—choosing specific ‘cultural partners’—represents an inherent limitation or a pragmatic strategy for navigating the region.